1, 2‐Benzothiazine Derivatives from Sulfonimidamides by Metal‐Catalyzed Annulation Reactions in Solution and under Solvent‐Free Mechanochemical Conditions. Issue 5 (21st January 2021) - Schöbel, Jan‐Hendrik; Elbers, Philipp; Truong, Khai‐Nghi; Rissanen, Kari; Bolm, Carsten
Abstract: Three‐dimensional aza‐analogues of 1, 2‐benzothiazine 1, 1‐dioxides have been prepared from sulfonimidamides. Two different protocols are presented. The first is a rhodium‐catalyzed annulation reaction with α ‐sulfonyloxyketones leading to 4‐unsubstituted benzothiazine derivatives. By selective bromination with NBS the heterocyclic ring can further be functionalized. In the second approach, an iridium catalyst is applied under solvent‐free mechanochemical conditions providing products with 3, 4‐disubstituted thiazine rings from diazoketo esters and diazoketo sulfones. Abstract :